THE MOVEMENT PATTERN AND HOME RANGE OF SUMATRAN ELEPHANTS (Elephas maximus ssp. sumatranus) IN THE LANDSCAPE OF MILA-TANGSE IN PIDIE REGENCY, ACEH - Tutia Rahmi; Kaniwa Berliani; Suwarno Suwarno (Forestry Study Program University Of Mataram, 2023)
The Sumatran elephant is the largest mammal species on the island of Sumatera. They are listed by the IUCN as critically endangered (IUCN, 2020). The current population throughout Sumatera lies on 22 home ranges and most of them are in critical condition (KLHK, 2020). One of the home ranges in Aceh Province is in the landscape of Mila-Tange, Pidie Regency. This landscape is a meeting point among the elephant herds. The herds that have been separated into small groups will gather with the other groups in several months. This phenomenon becoming one of the triggers for the incidents of human-elephant conflict. The conservation activity is being implemented by taking into account the needs of livelihood in the area. Therefore, the research was conducted to recognize the movement pattern and its range in this landscape during period of January to December 2021. The results show that the elephant herd range lies from 123 km2 to 413 km2. The movement patterns are concentrating in the type of shrubs (1.227 points which equal to 46.73%) and mixed dry land agriculture (923 points which equal to 35.15%). The roaming area and movement patterns are mostly influenced by the environmental factors including natural food, land cover and anthropogenic activities.